KETERKAITAN LOYALITAS PELANGGAN DAN KELANGSUNGAN BISNIS SERTA PERAN MEDIASI AKUNTABILITAS PRODUK - Kurnia Isnuwardiati; Pudjo Sugito (Eco-Entrepreneur, 2016)
The purpose of this study is to analyze the relationship of customer loyalty, business continuity and product accountability mediating role. The approach used in this study is a survey technique, a study that takes a sample of the population using questionnaires as the principal data collectors. The unit of analysis, all the small businesses in the outer circumference culinary Malang. The sample collection technique using proportional random sampling. From the nature of its relationship with other variables, consisting of exogenous variables, mediation and endogenous variables. Exogenous variables are variables that affect the variation of other variables, whereas endogenous variables are variables that variations influenced by other variables. Mediating variable nature strengthen or weaken the relationship between variables. In this study, the accountability of the product as a mediating variable, variable customer loyalty as exogenous and business continuity as an endogenous variable. Structural equation modeling analysis techniques used to analyze the data and simultaneously test theoretical models. Based on the results of data analysis revealed that loyalty pelanggn affect the continuity of business and product accountability uga role as mediating the effect of customer loyalty to the business continuity.